Control de un convertidor estático en sistemas fotovoltaicos interconectados (2011)
La búsqueda de fuentes de energía que ayuden a soportan los crecientes requerimientos energéticos sin sacrificar el medio ambiente es un punto importante dentro del desarrollo de la naciones. En este sentido fuentes de energía renovables como la energía solar aparecen como posibilidades energéticas inagotables y de gran interés gracias a su disponibilidad y al ser ambientalmente limpias. El esfuerzo está puesto en hacer estos métodos de generación de energía cada día más eficientes y económicos. Por tanto, una de las temáticas de mayor interés es el uso técnicas de seguimiento del punto de máxima potencia, para obtener la mayor cantidad de energía posible de un generador solar fotovoltaico dependiendo de las condiciones ambientales existentes. En este trabajo se presenta el diseño e implementación de un sistema solar fotovoltaico conectado a la red monofásica utilizando convertidores estáticos. Para esto se proponen dos métodos de seguimiento del punto de máxima potencia. El primero está basado en el uso de lógica difusa para sintetizar el algoritmo de seguimiento del punto de máxima potencia. El desempeño del método difuso se mejora mediante la ponderación de la acción de control por la corriente de corto circuito del generador fotovoltaico. Se propone una novedosa técnica basada en un modelo difuso Takagi-Sugeno del generador fotovoltaico que permite la estimación de la corriente de corto circuito sin tener que realizar un corto sobre el generador fotovoltaico. El segundo método propuesto usa el estimador de corriente de corto circuito para establecer una referencia en un sistema de control realimentado, aprovechando la proporcionalidad que existe entre la corriente de corto circuito y la corriente en el punto de máxima potencia. Los métodos se verifican mediante simulación y se construye un inversor, para la interconexión de un generador fotovoltaico a la red AC, que permite evaluar el desempeño de los métodos propuestos de forma experimental. / Abstract. Issues such as the increasing worry about global warming in despite of the increasing energy requirements imposed by the social and technological development have pointed the target toward sustainable energy resources free of greenhouse gas emissions. PhotoVoltaic energy plays an important role into the called green energies sources, reason why its use has been rapidly invigorated. However, a PV generator has two significant problems; the match between the load and the impedance of the PV generator to ensure the maximum power transfer, and the dependence of the weather conditions, such as solar irradiance and temperature; additionally regarding the low efficiency of a PV generator, is desirable to obtain the maximum power under any weather condition. To ensure the maximum power transfer, the load seen from the PV generator must be continuously adjusted. Therefore, a Maximum Power Point Tracking MPPT) algorithm must be implemented to achieve the match between the PhotoVoltaic generator and the load in real time, regarding that the maximum power point is not known a priori. Several Maximum Power Point Tracking MPPT methods have been proposed looking for more efficient Photovoltaic (PV) system. Some of them are simple but imply low efficiency compared with more sophisticated method. This document presents an intelligent fuzzy method for maximum power point tracking (MPPT) of a single grid-connected hotovoltaic system. The fuzzy inference system can easily synthesize the algorithm to perform MPPT. The MPPT fuzzy method is improved by weighting the control action by the short-circuit current. Hence, it is proposed an estimator of the short-circuit current based on a Takagi-Sugeno fuzzy model of the photovoltaic generator. The short-circuit current can be estimated under any weather condition in real time, without disconnecting the photovoltaic generator and measuring it. The short-circuit current is a simple method to achieve the maximum power point based on the fact that the current at the maximum power point is proportional to the short circuit current. Nevertheless, the measurement of the short circuit current implies high waste of energy. In this document a short circuit current estimator based on a Takagi-Sugeno fuzzy model of the PV array is proposed looking for overcoming the main disadvantages of the short circuit current method. The short-circuit current could be estimated under any weather condition in real time, without disconnecting the photovoltaic generator and measuring it. Simulation in a grid connected system shows attractive features such as high accuracy, and simple design. This method is validated by experiments using a two-stage single-phase, grid-connected inverter.